Factors Affecting The Income of Female Traders in The Informal Sector (Case Study: Traders at Amlapura Timur Market, Karangasem Regency) - Nyoman Ari Shita Sukmatari; Ida Ayu Nyoman Saskara (International Journal of Economics, Management and Accounting, 2025)
This study aims to analyze the factors that influence the income of female traders in the informal sector, specifically at Amlapura Timur Market, Karangasem Regency. The research employs a quantitative associative method using multiple linear regression analysis to examine the effects of age, working hours, capital, business location, and transportation costs on the income of female traders. Data were collected from 93 respondents using purposive sampling. The results show that age, working hours, capital, business location, and transportation costs simultaneously have a significant effect on the income of female traders. Partially, age has a negative effect on income, while working hours, capital, business location, and transportation costs have positive effects. This study provides insights into the challenges and opportunities faced by female traders in traditional markets and offers recommendations for gender- and location-based economic empowerment strategies.